Theoretical substantiation of the technology of developing future officers’ political competence at higher military educational institutions - Kuruch, A. (Problems of Engineer-Pedagogical Education, 2019)
The article considers a technology of developing political competence of future officers at military institutions of higher learning and proves the necessity of developing professional competence of modern officers as a constituent part of their professional training. Special attention is paid to the analysis of peculiarities of reforming higher military education in Ukraine. The paper also considers different approaches to education and upbringing technologies, as well as the structure of pedagogical technologies. The article focuses on the essence of the stages of the technology of developing political competence of future officers at higher military educational institutions and provides characteristics of the stages of the technology of developing political competence of future officers at higher military educational institutions, which are as follows: preparatory, motivational-purposeful, content-based, process- and activity-based, controlling-evaluative, each of the stages having its own aim, tasks and methods of implementation. The article proves the need to implement the technology of forming political competence of future officers at higher military educational institutions.